A concise route to the highly-functionalized azetidine precursor: the enantioselective synthesis of penaresidin B - Ding, Feiqing (2016)
An efficient and high-yielding synthesis of penaresidin B is disclosed herein. The concise 8-step synthesis of azetidine aldehyde was devised by incorporating our novel strategy for ready access to 3-amino-2,3-dideoxysugars via regio- and stereoselective tandem hydroamination/glycosylation of glycal as the key step.